Comparative Genomics of Pseudomonas sp. Strain SI-3 Associated With Macroalga Ulva prolifera, the Causative Species for Green Tide in the Yellow Sea - Fu, Huihui; Jiang, Peng; Zhao, Jin; Wu, Chunhui (Frontiers in Microbiology, 2018)
Algae-bacteria associations occurred widely in marine habitats, however, contributions of bacteria to macroalgal blooming were almost unknown. In this study, a potential endophytic strain SI-3 was isolated from Ulva prolifera, the causative species for the world's largest green tide in the Yellow Sea, following a strict bleaching treatment to eliminate epiphytes. The genomic sequence of SI-3 was determined in size of 4.8 Mb and SI-3 was found to be mostly closed to Pseudomonas stutzeri. To evaluate the characteristics of SI-3 as a potential endophyte, the genomes of SI-3 and other 20 P. stutzeri strains were compared. We found that SI-3 had more strain-specific genes than most of the 20 P. stutzeri strains. Clusters of Orthologous Groups (COGs) analysis revealed that SI-3 had a higher proportion of genes assigned to transcriptional regulation and signal transduction compared with the 20 P. stutzeri strains, including four rhizosphere bacteria, indicating a complicated interaction network between SI-3 and its host. P. stutzeri is renowned for its metabolic versatility in aromatic compounds degradation. However, significant gene loss was observed in several aromatic compounds degradation pathways in SI-3, which may be an evolutional adaptation that developed upon association with its host. KEGG analysis revealed that dissimilatory nitrate reduction to ammonium (DNRA) and denitrification, two competing dissimilatory nitrate reduction pathways, co-occurred in the genome of SI-3, like most of the other 20 P. stutzeri strains. We speculated that DNRA of SI-3 may contribute a competitive advantage in nitrogen acquisition of U. prolifera by conserving nitrogen in NH4+ form, as in the case of microalgae bloom. Collectively, these data suggest that Pseudomonas sp. strain SI-3 was a suitable candidate for investigation of the algae-bacteria interaction with U. prolifera and the ecological impacts on algal blooming.